Chloride salt sorption flux of cohesive sediment beds with different degrees of fluidization in quiescent water. (January 2022) - Yuan, Jing; Zheng, Binghui; Wang, Rui; Zhang, Minxi; Yu, Guoliang
Abstract: Cohesive sediments with different degrees of fluidization exhibit different rheological properties that affect chloride salt sorption in sediment and water columns. Recent studies have revealed that yield stress may be a more relevant parameter to describe the chloride salt sorption capacity of cohesive sediments at various degrees of sediment fluidization or consolidation. In this study, 365 experiments were performed to investigate the effects of sediment concentration and yield stress on chloride salt sorption flux in cohesive sediments. The results showed a negative power relationship between chloride salt sorption flux and yield stress. The chloride salt sorption flux increases with temperature, surface coefficient of fine particles, and the salinity difference between the sediment and water column. This study found that the sediment yield stress significantly affected the chloride salt sorption flux of the fluidized sediments. An empirical formula for the chloride salt sorption flux of cohesive sediment at various degrees of fluidization in quiescent water was proposed.